2015
DOI: 10.1002/biof.1197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bioactive properties of avenanthramide analogs produced in recombinant yeast

Abstract: Saccharomyces cerevisiae has been proven to be a valuable tool for the expression of plant metabolic pathways. By engineering a S. cerevisiae strain with two plant genes (4cl-2 from tobacco and hct from globe artichoke) we previously set up a system for the production of two novel phenolic compounds, N-(E)-p-coumaroyl-3-hydroxyanthranilic acid (Yeast avenanthramide I, Yav I) and N-(E)-caffeoyl-3-hydroxyanthranilic acid (Yeast avenanthramide II, Yav II). These compounds have a structural similarity with a class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 53 publications
(84 reference statements)
3
38
0
Order By: Relevance
“…In particular, oxidative stress has been clearly implicated in all the major molecular and cellular alterations related to CCM diseases, including destabilization of endothelial cell-cell junctions, increased β1 integrin activation, reduced cellular ability to maintain a quiescent state, increased vascular permeability, and angiogenic activity (Fraser, 2011, Fukai and Ushio-Fukai, 2011, Goitre et al, 2012, Ushio-Fukai, 2009), suggesting that it may represent a significant triggering factor involved in the initiation and progression of CCM disease. Consistently, CCM proteins have been involved in protecting cells against oxidative stress (Fidalgo et al, 2012, Goitre et al, 2010, Goitre et al, 2014), raising the possibility that CCM lesions may result from an impaired oxidative stress defense in microvascular districts of genetically predisposed subjects, and opening new therapeutic perspectives (Gibson et al, 2015, Goitre et al, 2010, Goitre et al, 2014, Moglia et al, 2015, Moglianetti et al, 2016). …”
Section: Redox Signaling and Oxidative Stress: The Two Emerging Facesmentioning
confidence: 98%
“…In particular, oxidative stress has been clearly implicated in all the major molecular and cellular alterations related to CCM diseases, including destabilization of endothelial cell-cell junctions, increased β1 integrin activation, reduced cellular ability to maintain a quiescent state, increased vascular permeability, and angiogenic activity (Fraser, 2011, Fukai and Ushio-Fukai, 2011, Goitre et al, 2012, Ushio-Fukai, 2009), suggesting that it may represent a significant triggering factor involved in the initiation and progression of CCM disease. Consistently, CCM proteins have been involved in protecting cells against oxidative stress (Fidalgo et al, 2012, Goitre et al, 2010, Goitre et al, 2014), raising the possibility that CCM lesions may result from an impaired oxidative stress defense in microvascular districts of genetically predisposed subjects, and opening new therapeutic perspectives (Gibson et al, 2015, Goitre et al, 2010, Goitre et al, 2014, Moglia et al, 2015, Moglianetti et al, 2016). …”
Section: Redox Signaling and Oxidative Stress: The Two Emerging Facesmentioning
confidence: 98%
“…On the other hand, Avn analogs produced in recombinant yeast, including YAvn I and YAvn II, were originally shown to have strong antioxidant activity when tested in an ABTS •+ radical quenching assay, as well as the capacity to reduce intracellular ROS levels in a cellular model of CCM disease, as evaluated with a cellular antioxidant assay [ 39 ]. Subsequent in vitro studies demonstrated that YAvn I and YAvn II positively regulate cell antioxidant defense mechanisms through the upregulation of forkhead box protein O1 (FOXO1) and superoxide dismutase 2 (SOD2) expression levels [ 40 ]. In addition, recent studies in an animal model of CCM disease have extended these findings, demonstrating the effectiveness of YAvns in major oxidative stress-related disease phenotypes [ 41 ] ( Table 1 ).…”
Section: Radical-scavenging and Antioxidant Activity Of Avenanthramentioning
confidence: 99%
“…Moreover, it was reported to inhibit proliferation, chemotaxis, and tube formation of human microvascular endothelial cells in vitro and angiogenesis in vivo [ 59 ], as well as vascular endothelial growth factor (VEGF)-induced vascular permeability [ 60 ], suggesting that it might ameliorate angiogenesis-related diseases, such as tumor metaplasia, rheumatoid arthritis, diabetic retinopathy, and age-related macular degeneration, acting as a novel angiogenesis inhibitor [ 59 , 61 , 62 ]. Finally, recent evidence demonstrates that recombinant YAvn I and YAvn II are endowed with stronger antiproliferative properties than natural Avns, including Avn-B, due to their enhanced capacity of reducing intracellular ROS levels and cyclin D1 expression [ 40 ] ( Table 3 ).…”
Section: Antiproliferative Activity Of Avenanthramidesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, engineered Escherichia coli strains have been developed to express BAHDs such as hydroxycinnamoyl-CoA:quinate transferases (HQT) for the synthesis of the antioxidant chlorogenic acid [6, 7]; hydroxycinnamoyl-CoA:hydroxyphenyllactate transferases for the production of rosmarinic acid [810]; hydroxycinnamoyl-CoA:glycerol transferase for the synthesis of the water-soluble antioxidants hydroxycinnamate glycerol esters [11] and hydroxycinnamoyl/benzoyl-CoA:anthranilate transferase (HCBT) for the production of therapeutic benzoyl and hydroxycinnamoyl anthranilates [12]. To our knowledge, the use of yeast strains engineered for the expression of BAHD acyltransferases has not been reported, except for the synthesis of hydroxycinnamoyl anthranilates using either HCBT or promiscuous hydroxycinnamoyl-CoA:shikimate transferases [1316].
Fig.
…”
Section: Introductionmentioning
confidence: 99%